Implementasi Metode Scrum (Agile) Pada Sistem Reservasi Fasilitas Olahraga Futsal Berbasis Mobile - Ali, Hilmi; Anita Fira Waluyo (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2024)
People's interest in sports is very significant in the current era, especially in futsal. However, booking a futsal field often experiences obstacles, such as limited operational time for phone or in-person booking. This situation hinders accessibility and convenience for users who want to make reservations. The Scrum method, as one of the frameworks in Agile-based software development, offers an iterative and structured approach. Scrum allows research to work collaboratively, divides faster research flows called sprints, and delivers results incrementally. From the results of research on futsal field reservation applications, it can be concluded that system development by applying the Scrum method significantly contributes to increasing efficiency and ease in the field reservation process. A success rate can be proven by testing the overall evaluation of the system against users where the total success percentage of all modules is 90.67%. The module with the highest percentage of success is Field Booking (100%), while the lowest is Payment (80%). There is input from users based on the evaluation results to focus on improving the stability of the Payment module to increase overall success.